THE INFLUENCE OF WHATSAPP ADVERTISEMENT ON PURCHASE DECISION TO INCREASE SALES OF LOCAL CULINARY PRODUCTS IN COVID-19 PANDEMIC PERIOD - Achmad, Gusti Noorlitaria; Adhimursandi, Doddy; Rahmawati, Rahmawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study examined the Influence of Online advertisement Via WhatsApp consisting of attitude towards the ad, ad recall and click through rates, against the decision of the purchase for the increased sales of Local Culinary Products. The purpose of this research was to describe the activity of young culinary entrepreneurs in social media that is WhatsApp the current phenomenon of increased numbers of their accounts as well as how much influence the activity of the young culinary entrepreneurs on WhatsApp can increase sales of local culinary products. With the right marketing activities on WhatsApp can be beneficial against purchasing decisions so that it will enhance local culinary products sales. This research use questionnaire as a research instrument to get the data from the consumer donut JCO. In this study the respondent's criteria are that respondents must be followers, and never eat the product by the number of samples planned is 100 people. Analysis tools that will be used Multiple Linear Regression is to test the influence of the dependent and independent variables. The results of the data processing have been done the third factor i.e. attitude towards the advertisement, ad recall and click rates are throught to have simultaneous and partial influence against the purchasing decision. Factor Ad Recall is the most dominant factor and Factor Click Through Rates is the factor that has the most influence diminished purchasing decisions